2019
DOI: 10.1002/1873-3468.13545
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense‐mediated mRNA decay of the ferric and cupric reductase mRNAs FRE1 and FRE2 in Saccharomyces cerevisiae

Abstract: The nonsense‐mediated mRNA decay (NMD) pathway regulates mRNAs that aberrantly terminate translation. This includes aberrant mRNAs and functional natural mRNAs. Natural mRNA degradation by NMD is triggered by mRNA features and environmental cues. Saccharomyces cerevisiae encodes multiple proteins with ferric and cupric reductase activity. Here, we examined the regulation by NMD of two mRNAs, FRE1 and FRE2, encoding ferric and cupric reductases in S. cerevisiae. We found that FRE2 mRNAs are regulated by NMD und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 26 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…The immunity to NMD‐mediated regulation of PCA1 970G is physiologically significant to yeast cells because this correlates with RM11‐1a tolerance to cadmium (Figure 1b). Furthermore, we have observed differential NMD‐mediated regulation of mRNA involved in iron homeostasis based on iron availability (M. Peccarelli et al, 2019). The FRE2 mRNAs encode a ferric and cupric reductase and are regulated by NMD under normal growth conditions but not under low iron conditions (M. Peccarelli et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The immunity to NMD‐mediated regulation of PCA1 970G is physiologically significant to yeast cells because this correlates with RM11‐1a tolerance to cadmium (Figure 1b). Furthermore, we have observed differential NMD‐mediated regulation of mRNA involved in iron homeostasis based on iron availability (M. Peccarelli et al, 2019). The FRE2 mRNAs encode a ferric and cupric reductase and are regulated by NMD under normal growth conditions but not under low iron conditions (M. Peccarelli et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, we have observed differential NMD‐mediated regulation of mRNA involved in iron homeostasis based on iron availability (M. Peccarelli et al, 2019). The FRE2 mRNAs encode a ferric and cupric reductase and are regulated by NMD under normal growth conditions but not under low iron conditions (M. Peccarelli et al, 2019). Altogether, these observations suggest that NMD‐mediated regulation of natural mRNAs that are responsive to environmental conditions depends on the following: (1) if the growth conditions are inducing or non‐inducing and (2) the function of the encoded protein in the specific growth conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because Mac1p is a transcription factor that activates genes under low copper conditions we would expect the downstream genes to be regulated by NMD like MAC1 , although they would be indirect NMD targets. CTR1 and FRE1 mRNAs are well characterized Mac1p targets and they should be indirect NMD targets under normal growth conditions where MAC1 mRNA is directly regulated by the pathway according to prototypical direct and indirect NMD targets (Figure 1B (16)). However, the model for direct and indirect NMD targets is not applicable here because the functionality of Mac1p is dependent on copper levels.…”
Section: Discussionmentioning
confidence: 99%
“…Many different stimuli can induce NMD-mediated degradation including nutritional metals such as copper and iron. We found that in S. cerevisiae NMD plays a role in copper and iron homeostasis (16-18). Understanding nutritional metal homeostatic mechanisms in yeast will provide insights into the regulatory mechanisms used by other organisms as these mechanisms have been conserved throughout evolution (19).…”
Section: Introductionmentioning
confidence: 94%